Diversity: A view from the conceptions of counseling professional collective. Challenges and dares - Cindy Vanessa Artavia-Aguilar; Luis Roberto Campos-Hernandez (Revista Electrónica Educare)
Social changes and new world paradigms require reflection on professional interventions in an increasingly diverse context. The analysis of the theory and practice of professional work in Guidance becomes a priority constant. This research aims to collect conceptions built on the diversity concept by a group of counselors during their professional excersice and from their experiences in the Costa Rican Education System and the research also tries to define the interventions and professional conditions necessary to meet diversity, as a concept, from the discipline. The research has a qualitative approach; it was performed with 10 professionals in Guidance of the Costa Rican Education System. They were selected by convenience and were interviewed using an open question questionnaire. The information obtained was systematized and presented in three categories related to analysis matrices: diversity concept, diversity in Counseling professional intervention and proposals and conditions to approach diversity from the discipline. The main findings focus on the reflection of professional work in developing the concept diversity as a socio-personal construct, the interventions rooted in daily practice and professional features to address diversity that are related to knowledge, sensitivity, innovation , flexibility, professional ethics and vocation.